Penerapan Algoritma LZ77 dan Algoritma Difference Coding Untuk Memperkecil Ukuran pada Citra Satelite Geoeye - Amanda Pratama; Muhammad Syahrizal (STMIK Budi Darma, 2020)
Geoeye satellite imagery is one of the satellite images that has a high resolution and is gaining in popularity in recent years. As one of the global satellite imagery, it is clear that this satellite image offers something that can amaze anyone of its users, this satellite image offers an earth surface image with a level of detail that can be considered extraordinary, and the level of accuracy after compared to satellite imagery that has high resolution the other